2021
DOI: 10.1093/europace/euaa390
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein isolation in a real-world population does not influence QTc interval

Abstract: Aims We aimed to examine whether routine pulmonary vein isolation (PVI) induces significant ventricular repolarization changes as suggested earlier. Methods and results Five-minute electrocardiograms were recorded at hospital’s admission (T−1d), 1 day after the PVI-procedure (T+1d) and at 3 months post-procedure (T+3m) from a registry of consecutive atrial fibrillation (AF) patients scheduled for routine PVI with different PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We thank Prof. Aksu for this valuable and well-balanced discussion on the possible effect of ablation of atrial ganglionated plexuses (GPs) on the QT interval. 1 Their comments are in line with our statement that from our study 2 we neither can conclude that pulmonary vein isolation (PVI) does not modulate GP nor that GP modulation leads to changes in QTc. We can, however, conclude that, on average, routine PVI does not induce changes in QTc.…”
supporting
confidence: 62%
“…We thank Prof. Aksu for this valuable and well-balanced discussion on the possible effect of ablation of atrial ganglionated plexuses (GPs) on the QT interval. 1 Their comments are in line with our statement that from our study 2 we neither can conclude that pulmonary vein isolation (PVI) does not modulate GP nor that GP modulation leads to changes in QTc. We can, however, conclude that, on average, routine PVI does not induce changes in QTc.…”
supporting
confidence: 62%
“…One study confirmed significant QTc prolongation by ~25 ms immediately after the atrial fibrillation ablation, by ~10–15 ms after 1 day, and by ~5–10 ms after 1 and 3 months (already nonsignificant) 2 . The other study did not find any meaningful change in QTc both after 1 day and 3 months following the atrial fibrillation ablation 3 . One may argue that such patients were much older and likely had more comorbidities compared to typical candidates of cardioneuroablation.…”
mentioning
confidence: 97%
“…that AAD might affect both the RR- and QT-interval in our study and could be an explanation for the differences in raw RR- and QT-intervals between their and our study. However, as we already mentioned in the discussion of our original paper, 2 we believe that our study population better reflects the real-world population of patients undergoing pulmonary vein isolation since these patients are frequently treated with AAD before ablation. Therefore, we believe we induce a bias if we would only include patients without AAD.…”
mentioning
confidence: 98%
“…We would like to thank you for the opportunity to respond to the issues raised in Dr Chikata’s letter titled ‘Does pulmonary vein isolation prolong QT-interval’. 1 In their letter to the editor, they raise three concerns regarding our study 2 which we will further discuss in this response: (1) the use of an automated algorithm to measure the QT-interval; (2) the use of antiarrhythmic drugs (AAD) in our study population, and (3) the heart rate correction methods for QT-intervals. 1…”
mentioning
confidence: 99%